ANALISIS FAKTOR RISIKO ERGONOMI PADA PEKERJA PT XYZ MENGGUNAKAN METODE REBA, WERA DAN OWAS - Florenza Josefine Hindarto; Lamto Widodo; I Wayan Sukania (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2025)
The advancement of digitalization and automation has accelerated production processes, but often overlooks human factors, thereby increasing ergonomic risks such as musculoskeletal disorders (MSDs) among production workers. This study was conducted at a technology industry company in Cakung, East Jakarta, focusing on production workers identified as having MSDs risks through direct observation. The novelty of this research lies in the use of four methods in analyzing work activities to determine the dominant risk factors through the selection of the highest scores, compared to other studies that tend to use one to two methods for analysis. The objective of this research is to determine the highest risk level from four types of work activities using four methods. Data collection methods include observation, the Nordic Body Map (NBM) questionnaire, and photograph documentation of work activities. Data analysis utilized Rapid Entire Body Assessment (REBA), Workplace Ergonomic Risk Assessment (WERA), and Ovako Working Posture Analysis System (OWAS). The questionnaire results indicate the highest complaints with very strong pain in the back (14%), waist (13%), buttocks (8%), lower neck (7%), right upper arm (6%), right wrist (6%), and left thigh (6%). The work activity analysis yielded risk scores: lifting product (REBA 9, WERA 34, OWAS 3), assembly (REBA 5, WERA 36, OWAS 1), labeling (REBA 4, WERA 33, OWAS 2), and final packing (REBA 10, WERA 45, OWAS 2). The conclusion in this study is that the work activities of lifting products and final packing pose the highest ergonomic risks and require immediate intervention to prevent ongoing musculoskeletal disorders.